Pengaruh Konseling Kelompok Adlerian Untuk Meningkatkan Self-Wareness Anak Di Panti Asuhan Muhammadiyah Koto Baru - syarifah, Indri; Masril (SENGKUNI Journal (Social Science and Humanities Studies), 2025)
This research originated from the fact that there are children at the Muhammadiyah Orphanage Koto Baru who have low self-awareness. The school counselor is one of the parties who strives to help students improve their self-awareness. The purpose of this study is to examine the level of self-awareness among children at the Muhammadiyah Orphanage Koto Baru and to assess the effectiveness of Adlerian group counseling in enhancing their self-awareness. This research is a pre-experimental study using the One-Group Pre-Test Post-Test design. The research sample consisted of eight children from the Muhammadiyah Orphanage Koto Baru who were identified as having low self-awareness. Data collection techniques involved a self-awareness scale. Data were analyzed using a paired t-test with the assistance of the Statistical Product and Service Solution (SPSS) version 25 and the N-Gain test. The findings of the study showed that the self-awareness of the children before receiving Adlerian group counseling (pre-test) was in the low category, and after receiving Adlerian group counseling (post-test), it increased to the moderate category. This indicates a difference in self-awareness before and after the group counseling intervention. Therefore, it can be concluded that Adlerian group counseling is effective in improving the self-awareness of children at the Muhammadiyah Orphanage Koto Baru. Based on these results, it is recommended that school counselors further develop guidance and counseling services, especially Adlerian group counseling, to help improve the self-awareness of children in orphanages.